CFD study of shock bump roughness for transonic shock control and buffet alleviation - Di Pasquale, Davide (American Institute of Aeronautics and Astronautics (AIAA), 2024)
Shock induced separation is a serious problem in the transonic flow regime which leads tobuffet - unsteady aerodynamic loading on the wing, that can cause serious structural fatigueand failure. These phenomena compromise the flight envelope and structural integrity ofan aircraft, and consequently its operational safety. One possible solution is to control anddelay the boundary layer separation. The aim of this work was to numerically study whethersub-boundary layer scale distributed roughness, arranged in periodic strips, which locallyincreases the boundary layer displacement thickness, can act as a virtual shock bump withthe aim of bifurcating the foot of the shock wave to reduce the shock’s adverse effect on theboundary layer. A full span bump (upper surface aerofoil shape) model mounted on the floor ofa transonic wind tunnel was previously tested with several configurations of such shock-bumproughness. This study performed steady Navier-Stokes CFD analysis of the working section flowto match the experimental data for the smooth surface bump, and then to assess the affect ofsimulated shock bump roughness. The performance of several turbulence models was comparedwith experimental data (Mach 0.55 inflow, Reynolds number based on bump chord between 3.1 -3.6 million) - the𝜅−𝜔SST model being found to be the most accurate for this type of problem. Itwas predicted that shock-bump roughness tends to move the shock wave downstream and reduceits strength in cases where the roughness elements are located directly under the interaction,as in the solid shock bump case. This suggests that the virtual displacement effect of surfaceroughness can be designed to provide the same shock-bump effect as a solid protuberance butpotentially without the extra weight and pressure drag. Shock-bump roughness arranged instrips aligned with the streamwise flow were predicted to perform better than those arranged ata 30 degree skew angle to the flow. No conclusive evidence from the numerical models showsthat shock-bump roughness can improve the separated flows if placed upstream of the shock, incases where the shock wave moved downstream of the roughness location.